2010
DOI: 10.1002/jcp.22220
|View full text |Cite
|
Sign up to set email alerts
|

High expression of IMPACT protein promotes resistance to indoleamine 2,3‐dioxygenase‐induced cell death

Abstract: Indoleamine 2,3-dioxygenase (IDO), a tryptophan degrading enzyme, is a potent immunomodulatory factor. IDO expression in fibroblasts selectively induces apoptosis in immune cells but not in primary skin cells. However, the mechanism(s) of this selective effect of IDO-induced low tryptophan environment is not elucidated. The aim of present study was to investigate whether the activity of general control non-derepressible-2(GCN2) kinase stress-responsive pathway and its known inhibitor, protein IMPACT homolog, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
(64 reference statements)
1
19
0
Order By: Relevance
“…Thus, in more differentiated cells, such as macrophages and Tregs, GCN2 activation has a signalling function [226,259], whereas GCN2-mediated cell cycle arrest adversely affects rapidly proliferating effector T-cells [225]. Studies with human T-cells and fibroblasts have identified that the sensitivity of cells to L-Trp starvation and GCN2-mediated apoptosis relates to the expression level of the protein IMPACT, an inhibitor of GCN2 kinase activity [262]. Accordingly, compared with fibroblasts, T-cells constitutively express low levels of IMPACT and, in response to low-L-Trp environments, exhibit higher levels of GCN2 activation and apoptosis; IMPACT gene overexpression of T-cells protected against L-Trp deficiency, whereas gene knockdown of IMPACT in fibroblasts rendered these cells more sensitive to low L-Trp [262].…”
Section: Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in more differentiated cells, such as macrophages and Tregs, GCN2 activation has a signalling function [226,259], whereas GCN2-mediated cell cycle arrest adversely affects rapidly proliferating effector T-cells [225]. Studies with human T-cells and fibroblasts have identified that the sensitivity of cells to L-Trp starvation and GCN2-mediated apoptosis relates to the expression level of the protein IMPACT, an inhibitor of GCN2 kinase activity [262]. Accordingly, compared with fibroblasts, T-cells constitutively express low levels of IMPACT and, in response to low-L-Trp environments, exhibit higher levels of GCN2 activation and apoptosis; IMPACT gene overexpression of T-cells protected against L-Trp deficiency, whereas gene knockdown of IMPACT in fibroblasts rendered these cells more sensitive to low L-Trp [262].…”
Section: Lymphocytesmentioning
confidence: 99%
“…Studies with human T-cells and fibroblasts have identified that the sensitivity of cells to L-Trp starvation and GCN2-mediated apoptosis relates to the expression level of the protein IMPACT, an inhibitor of GCN2 kinase activity [262]. Accordingly, compared with fibroblasts, T-cells constitutively express low levels of IMPACT and, in response to low-L-Trp environments, exhibit higher levels of GCN2 activation and apoptosis; IMPACT gene overexpression of T-cells protected against L-Trp deficiency, whereas gene knockdown of IMPACT in fibroblasts rendered these cells more sensitive to low L-Trp [262]. Further studies are clearly required into how L-Trp starvation and GCN2 signalling influences cellular function and viability of other IDO1-expressing cell types and the molecular signalling mechanisms involved.…”
Section: Lymphocytesmentioning
confidence: 99%
“…Some MDSC subsets have been shown to express indoleamine 2,3 dioxygenase (IDO), depleting the microenvironment of tryptophan, and through expression of inducible nitric oxide synthase (iNOS) and arginase-1, l-arginine that serves as a substrate for both enzymes, is depleted from the microenvironment [8]. Importantly, T cells are particularly sensitive to amino acid deprivation [9]. In addition, nitric oxide (NO), a product of l-arginine catabolism by iNOS, is in itself able to suppress T-cell function.…”
Section: Introductionmentioning
confidence: 99%
“…Indoleamine 2, 3 dioxygenase (IDO), similarly to ASNase and borrelidin, induces amino acid deprivationmediated stress in cells through catabolism of tryptophan. It has been shown that the apoptotic effects of IDO on immune cells are at least in part due to the selective activation of the GCN2 kinase pathway in these cells [19][20][21].…”
Section: Introductionmentioning
confidence: 99%